Biosynthesized Silver Nanoparticles from Glycosmis pentaphylla (Retz.) DC.: A Multifunctional Nanomedicine for Antioxidant, Antidiabetic and Anticancer Therapeutics - Shafiulla, Abdul; Kumar G T, Mahanthesh; C K, Ramesh; Mohammed, Riaz (International Journal of Aquatic Research and Environmental Studies, 2026)
Glycosmis pentaphylla (Retz.) DC., a medicinal plant widely distributed in tropical regions and traditionally used in Ayurveda and folk medicine, is known for its rich phytochemical profile comprising alkaloids, flavonoids, terpenoids, and phenolic compounds with reported antioxidant, antimicrobial, antidiabetic, and anticancer activities. Leveraging its bioactive constituents, the present study employed an eco-friendly green synthesis approach for the fabrication of silver nanoparticles (AgNPs) using Glycosmis pentaphylla bark extract as a natural reducing and stabilizing agent, followed by detailed physicochemical characterization and biological evaluation. The formation of AgNPs was confirmed by UV–visible spectroscopy through the appearance of a characteristic surface plasmon resonance band. Fourier-transform infrared (FTIR) analysis indicated the involvement of phenolic, hydroxyl, and amine functional groups in nanoparticle reduction and surface capping. Scanning electron microscopy (SEM) revealed nanoscale morphology with moderate aggregation, while X-ray diffraction (XRD) confirmed the crystalline face-centered cubic structure of metallic silver. Energy-dispersive X-ray (EDX) spectroscopy, particle size analysis (PSA), and zeta potential measurements further validated the elemental composition, nanoscale size distribution, and colloidal stability of the synthesized nanoparticles. Biological assessments demonstrated concentration-dependent antioxidant activity in DPPH and hydrogen peroxide scavenging assays. The AgNPs exhibited significant α-amylase inhibitory activity and enhanced glucose uptake, indicating promising antidiabetic potential. In vitro cytotoxicity studies revealed moderate yet selective antiproliferative effects against MDA-MB-231, A549, and KB-3-1 cancer cell lines, with comparatively lower toxicity toward normal L929 fibroblast cells. Additionally, the wound healing assay confirmed enhanced cell migration and wound closure following nanoparticle treatment. Overall, the findings highlight that Glycosmis pentaphylla-mediated AgNPs combine phytochemical functionality with nanoscale properties, resulting in multifunctional therapeutic potential. This study underscores the translational value of medicinal plant-based nanomaterials for future biomedical and nano pharmaceutical applications.
Keywords: Green synthesis, silver nanoparticles, phytochemical-mediated reduction, antioxidant activity, Cytotoxicity, Wound healing, nanomedicine.